2235. Discordance of Clinical and Microbiological Endpoints in Clinical Trials for Complicated Urinary Tract Infection (cUTI). (15th December 2022) - Kadry, Nadia A; Natarajan, Mukil; Bein, Edward; Kim, Peter; Farley, John
Abstract: Background: Complicated urinary tract infections (cUTI) are a clinical syndrome characterized by pyuria and a documented microbial pathogen on urine or blood culture, accompanied by local and systemic signs and symptoms, in the presence of urinary tract abnormalities or acute pyelonephritis. Current FDA guidance recommends that the primary endpoint for cUTI clinical trials be a composite of the clinical and microbiological responses, assessed at a fixed time after therapy. In recent trials, it has been noted that while some patients have clinical resolution of symptoms, they are considered failures due to positive urine cultures. These discordant outcomes have raised questions about the utility of the microbiological endpoint. Methods: We analyzed patient data from 13 phase 3 clinical trials submitted to the FDA. We focused on the microbiological modified intent-to-treat (m-MITT) population, including patients who have at least 1 bacterial pathogen known to cause cUTI and received at least one dose of study drug (N=4842). Outcomes were determined at the Test of Cure (TOC) visit 7-10 days after therapy, and the Late Follow Up (LFU) visit 3-4 weeks after therapy. Clinical and microbiological success were defined as the resolution of cUTI symptoms present at entry, with no new symptoms (clinical cure), and reduction of the pathogen at entry to ≤ 10 3 CFU/mL on urine culture (microbiological eradication). Results: Among all included patients, 70.7% were overall successes at the TOC, exhibiting clinical and microbiological success. 18.0% were discordant failures (clinical cure/microbiological persistence), and 6.7% were concordant failures (clinical failure/microbiological persistence). In a multivariate logistic regression model, discordance was associated with obesity, lithiasis, use of analgesics, and receipt of carbapenem antibiotics. Discordant patients were at an increased risk for clinical failure at the LFU visit, and the risk of late clinical failure increased with longer time between the TOC and LFU visits. Conclusion: Microbiological persistence at the TOC visit despite resolution of symptoms was associated with an increased risk of late clinical failure. Microbiological outcomes appear to be an important component in the composite endpoint. Disclosures: All Authors : No reported disclosures.